Hematologic variation values of captive red-footed tortoise (chelonoidis carbonaria) in South Brazil - da Silva Bergamini, Bruno Carvalho [UNESP]; dos Santos, Elisandro Oliveira; Wartchow, Bárbara Schiller; Heck, Lilian; Uhrig, Luiza; Francelino, Lygia Karla Sanches; Stein, Gisele Guiomara; Machado, Gustavo; de Faria Valle, Stella (My University, 2017)
Background: Reference hematological values for chelonians are uncommon, especially those that take account of seasonal variations. While there exists controversy over how climate influences hematological values in different reptile species, the identification of this influence would help with the diagnosis, treatment, and prognosis of diseases that affect these species, often kept as pets. Chelonians are ectotherms and, therefore, intrinsic and extrinsic factors may affect physiological and hematological values, affecting the interpretation of clinical information on these species. The aims of this study were to assess the hematological values of captive red-footed tortoises (Chelonoidis carbonaria) and to check their variation according to the cold and warmer seasons of the year. Materials, Methods & Results: Blood samples were collected from nine red-footed tortoises (C. Carbonaria) of indeterminate sex and different ages, bred in captivity without control over environmental variables during one year, one each season (summer, fall, winter and spring). A total of 36 samples were considered to study. The colder seasons were collapsed together into one group that holds winter and fall (colds) and the months whit warmer weather spring and summer were grouped as a class called (warm). The complete blood count was performed manually, and medians, maximum values, and minimum values were obtained from the animals in each season of the year. The samples were grouped in cold and warm classes as above. Repeated measures ANOVA were used in order to compare the influence of climate variation on hematologic variables. For this mater Bonferroni's test was employed as post-hoc analysis. As results, the erythrocytes total count, hemoglobin value, hematocrit, mean corpuscular hemoglobin concentration, absolute numbers of heterophils, eosinophils, basophils, monocytes, and total plasma proteins varied significantly (P < 0.05) between colder and warmer seasons. Erythrocyte values yielded significantly higher values in warmer seasons than in the other seasons. The seasonality was verified in erythrocytes total count (P < 0.001), hemoglobin value (P < 0.001), hematocrit values (P < 0.001) and differential white blood cell count (P < 0.001). Discussion: The hematological alterations detected in C. carbonaria were similar observed in similar studies in reptiles species and due to the distinct method and management used and different species, it was not possible to compare the statistical results. In previously studies, as a C. carbonaria, the hematological variations between climatic seasons were identified in other reptile species due particular ectothermic metabolism. The variation in total WBC count produced by seasons of the year had already been described in snakes, such as in South American rattlesnakes and in tropical snakes. Changes in metabolic activity may be influence in TPP values in reptiles when season of the year is included as a variable. In hibernating species, the variation in TPP values is attributed to hibernating behavior when the lower food intake led to a decrease in plasma protein levels. In the case of C. carbonaria, which does not hibernate, other variables could influence the difference between seasons. All hematological changes observed in studied animals confirm the influence of climate between cold and hot months, given the peculiar metabolism of chelonians. The results point out the importance is to consider the seasonal climate variations in the interpretation of hematological values of C. carbonaria under uncontrolled environmental conditions.
Keywords: Chelonians; Climate variation; Complete blood count; White blood cell count